She could or she didn't? A revisionist analysis of the failure of the Widow Remarriage Act of 1856? - Indraneel Dasgupta; Diganta Mukherjee (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2006)
Under pressure from a progressive social movement, the British government in Bengal passed the (Hindu) Widow Remarriage Act in 1856. Yet few such remarriages subsequently occurred. Standard explanations for this failure rest on demand side arguments – few contemporary men were enlightened enough to wish to marry widows. We question this hypothesis. Using Census data from 1881, we argue that far too many contemporary men were single for it to be plausible. We advance a supply-side hypothesis instead – far too many men wished to marry widows for predatory reasons. This made it rational for widows (or their parents) to withdraw from the marriage market. Thus, the marriage market failed to implement feasible welfare gains from remarriage due to problems of informational asymmetry. We formalize our argument in terms of a simple model of adverse selection.
Keywords: 330; Widow Remarriage; Dowry; Polygamy